Fasciopatia plantar: investigando o papel da rigidez miofascial - Daniel Barreto Rabelo (2022)
Introduction: Plantar fasciitis or plantar fasciopathy (PF) is clinically characterized by pain in the plantar region, especially in the medial region of the calcaneus. One of the factors related to the structure and function of the body that may be related to the condition is the altered stiffness in myofascial meridian, known as the Posterior Superficial Line (PSL). Objective: To investigate whether there is a difference in the myofascial stiffness of the lower portion of the PSL of the symptomatic lower limb compared to the asymptomatic in individuals diagnosed with PF and to compare the myofascial stiffness data between individuals diagnosed with PF and asymptomatic individuals with no history of PF. Method: This is a cross-sectional observational study including individuals diagnosed with unilateral PF and asymptomatic individuals. Data on PSL meridian myofascial stiffness, assessed with the IdentoPro, and clinical tests were collected from both groups and lower limbs. A linear regression analysis with 1 between-group factor (groups) and 1 within-group factor (side) was performed. Mean differences (MD) and 95% confidence interval (CI) were calculated. Results: A total of 80 individuals, 41 individuals diagnosed with PF and 39 asymptomatic individuals, participated in the study. For 6 cm above the calcaneal tendon insertion, individuals with PF showed lower stiffness (MD= 0.56 N/mm; 95%CI: 0.10; 1.02) in the symptomatic side compared to the asymptomatic side and lower stiffness (MD= 1.00 N/mm; 95%CI: 0.21; 1.80) in the symptomatic side compared to the corresponding symptomatic side in the control group. For plantar fascia, individuals with PF showed higher stiffness (MD= 0,16: 95%CI: 0.01,0.30) in the asymptomatic side compared to the symptomatic side. For the 3cm above the calcaneal tendon insertion, individuals with PF showed lower stiffness than the asymptomatic individuals. Conclusion: Overall, our results support the lower stiffness in the plantar fascia and calcaneus tendon. Nevertheless, these differences may depend on tendon region or if the comparison is between individuals with and without PF or between the symptomatic and asymptomatic limbs.